慢性腎不全患者の口底部蜂窩織炎を契機として観察された腎性骨異栄養症の1例 - 小林, 正治; 西山, 秀昌; 小田, 陽平; 中村, 彬彦; 羽賀, 健太; 金丸, 祥平 (日本口腔外科学会雑誌, 2019)
Renal osteodystrophy (ROD) is characterized by specific changes in bone morphology in patients with end-stage renal failure and develops as a result of alterations in the metabolism of calcium and phosphate, or secondary hyperparathyroidism．　We report a case of ROD detected with cellulitis of the floor of the mouth. An 82-year-old man was referred to our department because of swelling of the floor of the mouth. The patient had been given a diagnosis of with chronic renal failure and treated. Blood tests showed severe renal dysfunction and increases in inflammatory markers and intact parathyroid hormone (PTH). Computed tomography images showed findings of osteolysis and osteosclerosis in the mandible. Therefore, the patient was given a diagnosis of ROD. He was admitted and immediately received antibacterial chemotherapy and drainage. Then his symptoms improved, and he was discharged on day 22．　On 1 year 2 months after first visit，the calcium and phosphate levels in blood tests were maintained within the normal range, and bone formation was observed in the mandible.　It is important to perform careful follow up because patients with ROD tend to have an increased risk of infection.